Fall detection systems at night - Elagovan, Ramanujam; Perumal, Thinagaran; Krishnan, Shankar (Institute of Electrical and Electronics Engineers, 2023)
Daytime-based fall detection systems (FADEs) are designed to prevent falls and help individuals carry out their activities independently. However, FADE for nighttime use is still a challenge for researchers. This article reviews various FADE systems and categorizes the open challenges for the design of nighttime-based FADE.